2012
DOI: 10.21914/anziamj.v53i0.5097
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning in parallel for fractional step Navier--Stokes solvers

Abstract: Preconditioning for the Pressure Poisson Equation, used with the fractional step Navier-Stokes solvers, is studied. The Pressure Poisson Equation results from the segregated calculation of the velocity and pressure in the momentum equations, with the divergence of the velocity as the source term. The coefficient matrix of the Pressure Poisson Equation is dependent only upon grid-size, and thus preconditioners need to be constructed only once initially, and used for all subsequent time steps. Several preconditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Those parameters were chosen from the optimum value for this case, which were obtained from preliminary tests. As the previous study [4] has shown that the optimum defined pattern depends on grid spacing or ratio, the pattern chosen here includes cell dependencies in the y direction only, omitting the dependencies in x and z directions. The SAI method includes 11 elements in each row of the preconditioner matrix, consisting of the diagonal element and 10 elements representing the dependencies to each 5-cells above and below the respective cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those parameters were chosen from the optimum value for this case, which were obtained from preliminary tests. As the previous study [4] has shown that the optimum defined pattern depends on grid spacing or ratio, the pattern chosen here includes cell dependencies in the y direction only, omitting the dependencies in x and z directions. The SAI method includes 11 elements in each row of the preconditioner matrix, consisting of the diagonal element and 10 elements representing the dependencies to each 5-cells above and below the respective cell.…”
Section: Methodsmentioning
confidence: 99%
“…[3]. The effectiveness of preconditioners on the parallel pressure correction method for turbulent channel flow was studied in [4]. In that study, the sparse approximate inverse with defined sparsity pattern was found to have comparable performance to the adaptive approach.…”
Section: Introductionmentioning
confidence: 99%